(untitled) (Journal of Partial Differential Equations, 2010)
In this work, we study the similarity analysis of the generalized nonlinear Burgers' equation having diffusivity and viscosity as a general functions of the particle velocity. We perform the symmetry analysis and exhibit exact solutions for various forms of the diffusivity and viscosity.